2013
DOI: 10.1039/c3cc41953c
|View full text |Cite
|
Sign up to set email alerts
|

Salt concentration, pH and pressure controlled separation of small molecules through lamellar graphene oxide membranes

Abstract: For the first time, pressure, salt concentration and pH demonstrated advantages for tuning the nanochannels within lamellar graphene oxide (LGO) membranes to control the separation of small molecules. This provides a new avenue for designing and engineering efficient LGO membranes for molecular separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
256
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 386 publications
(272 citation statements)
references
References 16 publications
14
256
1
1
Order By: Relevance
“…S1a) were prepared via a modified Hummers' method (see details in the Methods section), and GO membranes ( Supplementary Fig. S1b) were prepared using vacuum filtration 18 . The thickness of the membranes was adjusted by tuning the volume of GO suspension to be filtrated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1a) were prepared via a modified Hummers' method (see details in the Methods section), and GO membranes ( Supplementary Fig. S1b) were prepared using vacuum filtration 18 . The thickness of the membranes was adjusted by tuning the volume of GO suspension to be filtrated.…”
Section: Resultsmentioning
confidence: 99%
“…Laminated GO-based membranes assembled using micrometre-sized GO sheets exhibit distinguished characteristics, including hydrophilism, outstanding mechanical strength and good flexibility, which make GO an ideal candidate for nanoscale filtration and sieving applications 18 . For example, Geim and coworkers observed that submicrometre-thick free-standing GO membranes were completely impermeable for gases, including He, H 2 , N 2 and Ar.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior leads to the expansion of the interlayer space and indirectly adjusts the separation efficiency of the GO membrane. 68 A hybridization strategy can also provide better permeation performance of the GO stacked membrane. By the inclusion of positively charged Cu(OH) 2 nanostrands or nanosized carbon dots in a GO stacked membrane, the water permeability rises several-fold higher.…”
Section: Multilayer Graphene Desalination Membranesmentioning
confidence: 99%
“…23 However, the critical size of 0.9 nm is too large for the separation of small hydrated ions. Therefore, GO membranes have been used mainly for blocking large organic dyes and nanoparticles thus far, [24][25][26] whereas for most commonly available ions in solutions, GO membranes fail to act as a molecular sieve. Considering the charged nature of ions, it is possible to utilize electrostatic interactions between ionized oxygen functional groups (for example, carboxyl) and ions to generate selectivity for the filtration and separation of ions with different valences.…”
Section: Introductionmentioning
confidence: 99%